Left ventricular relaxation and filling in hypertrophic cardiomyopathy. An echocardiographic study. - Sanderson, J E (1978)
Echocardiograms showing left ventricular cavity and mitral valve cusps simultaneously were recorded in 36 patients, apex cardiograms being obtained in 26 of them. These were digitised and continuous plots made of left ventricular dimension, its rate of change, and anterior mitral leaflet velocity, and were compared with those in 20 normal subjects. Peak mitral diastolic closure rate was reduced to 120 +/- 80 mm/s, compared with normal (250 +/- 60 mm/s). Peak rate of increase of dimension was normal (13.4 cm/s), though the pattern of filling was disturbed, with the duration of rapid filling prolonged in 5, and shortened in 15, suggesting restriction. Mitral valve opening, normally synchronous with minimum dimension, was delayed by a mean of 76 ms, and during this period there was an abnormal increase in dimension. Dimension also increased by 50 +/- 25 per cent of the total diastolic excursion before the 'O' point of the apex cardiogram compared with 21 +/- 7 per cent in normals, and the timing of peak rate of increase of dimension was delayed by 50 +/- 20 ms instead of being synchronous with the 'O' point as normal. None of these findings correlated with the reduction in peak mitral diastolic closure rate. Noninvasive methods thus show that relaxation may be abnormal in hypertrophic cardiomyopathy. Delay in mitral valve opening and disturbances in the rate, duration, and co-ordination of wall movement during filling suggest the presence of segmental abnormalities of left ventricular function.